Yhteiskehittämisestä kilpailuetua matkailu- ja ravitsemisalalle - Mäntysaari, Anne; Törn-Laapio, Anne; Siltanen, Henna; Hauvala, Hanna; Heikkilä, Hilkka; Heikkilä, Tuija; Kupiainen, Tarja; Lahti, Elisa; Lassila, Hilkka, 1956-; Lindell, Mikael; Mantere, Päivi, 1966-; Mertanen, Enni, 1957-; et al. (Jyväskylä : Jyväskylän ammattikorkeakoulu, 2019)
Abstract.
Keywords: matkailuala; ravitsemisala; ammattikorkeakoulut; elinkeinoelämä; yhteistyö; kehittäminen; soveltava tutkimus